New insights into the role of mast cells as a therapeutic target in cancer through the blockade of immune checkpoint inhibitors - Ribatti, Domenico (Frontiers in Medicine, 2024)
Mast cells release different anti-and pro-inflammatory agents changing their role from protective to pro-inflammatory cells involved in the progression of different pathological conditions, including autoimmune diseases and tumors. Different mediators released by mast cells are involved in their biological activities which may be anti-tumorigenic and/or pro-tumorigenic. For these reasons, tumor mast cells have been considered a novel therapeutic target to prevent tumor progression and metastatic process. Many different agents have been suggested and used in the past pre-clinical and clinical settings. Among the novel immunotherapeutic approaches to cancer treatment, different immune checkpoint inhibitors targeting PD-1/PDL-1 have been used in the treatment of many human tumors improving overall survival. In this context, inhibition of mast cell activity may be considered a novel strategy to improve the efficacy of anti-PD-1/PDL-1 therapy. The blockade of the PD-1/PD-L1 interaction may be suggested as a useful and novel therapeutic approach in the treatment of tumors in which mast cells are involved.